Factors influencing demand for condominium in Penang, Malaysia - Abu Zarin, Hasmah; Bujang, Ahmad Ariffian (1998)
Condominium development had been facing a lot of pressure now, in Malaysia, due to the softening of the property market. This has affected the demand for this type of the property. Developers are facing more challenges in selling condominium units built due to buyers being more selective. Buyers are more particular in their purchasing decisions and use stricter criteria in investing their money to buy condominium units. This has given rise to the need for the developers to assess the specific factors that influence the demand for condominium in Penang, West Malaysia. This small island is focussed because it is perceived that factors influencing demand for condominium in this state are rather different compared to other states due to its nature as an island and due to its geographic location. the study uses questionaires to elicit information from the condominium buyers in the state. SPSS package was used to analyse the data. The study concludes that besides price beach scenary is one of the major factors determining demand for condominium in Penang island compared to states in the mainland.